Role of Cr2O3 on formation of reaction sintered dense ZrO2–Al2O3–SiO2 based refractory materials. (October 2013) - Chandra, D; Mishra, B; Das, G C; Sengupta, U; Maitra, S
Abstract : Extremely dense zirconia–mullite composites were developed by reaction sintering of microcalcined fine alumina powder and zircon flour taken in different ratios with Cr2 O3 as an additive. The powder mixes were isostatically pressed and sintered at 1550°C. The sintered compacts were characterised by different physicomechanical properties, microstructure developed and phase compositions. Cr2 O3 exhibited positive influence up to certain level of addition on the thermomechanical properties of reaction sintered zirconia–mullite composites including corrosion resistance and microstructure. On a développé des composites extrêmement denses de zircone et mullite par frittage réactif de poudre fine d'alumine micro calcinée et de farine de zircone en différentes proportions, avec du Cr2 O3 comme adjuvant. On a pressé les mélanges de poudres au moyen d'une presse isostatique et on les a frittés à 1550°C. On a caractérisé les différentes propriétés physico mécaniques, la microstructure développée et la composition de phases des compacts frittés. Le Cr2 O3 exhibait une influence positive jusqu'à un certain niveau d'addition sur les propriétés thermomécaniques des composites de zircone et mullite à frittage réactif, incluant la résistance à la corrosion et la microstructure.